A multisectoral food-assisted maternal and child health and nutrition program targeted to women and children in the first 1000 days increases attainment of language and motor milestones among young Burundian children - Olney, Deanna K.; Leroy, Jef L.; Bliznashka, Lilia; Ruel, Marie T. (Elsevier, 2019)
Child development is affected by multiple factors throughout pregnancy and childhood. Multisectoral programs addressing these factors may improve children's development.